Clinical Features and Burden Scores in Japanese Pediatric Migraines With Brainstem Aura, Hemiplegic Migraine, and Retinal Migraine. (September 2020) - Yamanaka, Gaku; Go, Soken; Morichi, Shinichiro; Takeshita, Mika; Morishita, Natsumi; Suzuki, Shinji; Tomoko, Takamatsu; Kasuga, Akiko; Daida, Atsuro; Ishida, Yu; Oana, Shingo; Suganami, Yusuke; et al.
Background: Migraines are a broad spectrum of disorders classified by the type of aura with some requiring attentive treatment. Vasoconstrictors, including triptans, should be avoided in the acute phase of migraines with brainstem aura, in hemiplegic migraine, and in retinal migraine. This study investigated the characteristics and burden of these migraines. Methods: Medical charts of 278 Japanese pediatric patients with migraines were retrospectively reviewed. Migraine burden of migraines with brainstem aura, hemiplegic migraines, and retinal migraine was assessed using the Headache Impact Test-6™ (HIT-6) and the Pediatric Migraine Disability Assessment scale (PedMIDAS). Results: Of 278 patients screened, 12 (4.3%) patients with migraines with brainstem aura (n = 5), hemiplegic migraines (n = 2), and retinal migraine (n = 5) were enrolled in the study. All patients had migraine with/without typical aura, whereas some patients had coexisting migraine with another type of headache (chronic tension-type headache in 3 patients, and 1 each with frequent episodic tension-type headache, headache owing to medication overuse, and chronic migraine). Migraines with brainstem aura, hemiplegic migraines, and retinal migraine patients with coexisting headaches had higher HIT-6 or PedMIDAS scores, whereas migraines with brainstem aura, hemiplegic migraines, and retinal migraine patients without coexisting headache did not show high HIT-6 or PedMIDAS scores. Conclusion: All migraines with brainstem aura, hemiplegic migraines, and retinal migraine patients experienced migraine with or without typical aura, and some patients having other coexisting headaches also had high PedMIDAS and HIT-6 scores. PedMIDAS and HIT-6 should not be considered diagnostic indicators of migraines with brainstem aura, hemiplegic migraines, or retinal migraine. In clinical practice for headaches in children, careful history taking and proactive assessment of the aura are needed for accurate diagnosis of migraines with brainstem aura, hemiplegic migraines, and retinal migraine.